ANALISIS KENDALA DARI HASIL EVALUASI EUCS: UPAYA MENGANTISIPASI POTENSI KEKURANGAN PADA PENGEMBANGAN SISTEM INFORMASI DI MASA DEPAN - Hermila A.; Rahmat Taufik R.L Bau; Saputra, Andi Muh Akbar (Jurnal Pekommas, 2023)
This research aims to analyze the constraints that arise from the EUCS (End-User Computing Satisfaction) evaluation results and to propose measures to anticipate potential shortcomings in future information system development. In the context of ongoing digital transformation, information system plays an increasingly important role in supporting organizational success. However, constraints from EUCS evaluation results are often overlooked, which can negatively impact the quality of information system development. Through an in-depth analysis of the identified constraints, this research uses the narrative review method to identify constraints that could potentially recur in the future. Furthermore, this research proposes steps that can be taken to anticipate potential shortcomings in future information system development. The author found the obstacles that tend to recur are the completeness of information (content), information that is not up to date (accuracy), monotonous appearance (format), the use of systems that are not easy to learn (ease of use), and long response time (timeliness). So, in the future, this can be a concern when designing an information system